Feasibility of duodenal balloon-assisted direct cholangioscopy with an ultrathin upper endoscope - Mori, A.; Ohashi, N.; Nozaki, M.; Yoshida, A. (Endoscopy, 2012)
Background and study aims: We have previously developed duodenal balloon-assisted direct cholangioscopy (DBA-DC) with an ultrathin endoscope (UTE). Here, we further evaluated the feasibility, safety, and diagnostic and therapeutic usefulness of DBA-DC using UTE.Patients and methods: 40 consecutive patients with biliary diseases were enrolled in a prospective observational feasibility study. We assessed the success rate, procedure time, durability of the UTE, and usefulness in diagnosis and therapy. We also evaluated safety, including cardiovascular alterations and biliary injury as complications of the procedure.Results: DBA-DC was performed successfully in 37/40 patients (92.5 %). The mean time to reach either biliary bifurcation or stricture was 11.8 ± 6.3 minutes. The procedure revealed 26 biliary stones, 5 cholangiocarcinomas, and 3 benign biliary strictures. Therapeutic procedures were performed in 16 patients (10 biliary lithotomies, 3 holmium-YAG laser lithotripsies, and 3 intraductal stent placements). No significant clinical complications related to DBA-DC were observed. Changes in cardiovascular responses and biliary biochemical parameters were minimal, except for leukocytosis in 8 patients.Conclusions: DBA-DC appears to be sufficiently feasible and may be useful as an alternative technique in cases that elude successful diagnosis and/or therapy with conventional endoscopic retrograde cholangiopancreatography (ERCP).